MANAJEMEN PEMBELAJARAN INTERNATIONAL BACCALAUREATE PRIMARY YEARS PROGRAMS IN SURABAYA INTERCULTURAL SCHOOL - Rachmad Priyadi (Prodi Magister Manajemen Universitas Wijaya Putra, 2017)
This research is purposing to find out how is the learning management of IB PYP in Surabaya Intercultural School (SIS) starting with the planning, applying and evaluating. This research is also uncovering the supporting elements and obstacles of the applying IB PYP in SIS. This is a qualitative research. The research is happening at Surabaya Intercultural School, Citra Raya Surabaya. The data is collected through observing, deep interviewing and documenting. The subjects of this research are elementary principle, curriculum coordinator and elementary teachers. The result of this research indicates that from the education management point of view SIS has a strong curriculum foundation that make the learning process run well. The curriculum is well-written in Atlas Rubicon (software). The curriculum mapping is done by individual teacher with guidance from the curriculum coordinator. In this curriculum all elements of learning from planning until evaluating are written well in software. All teacher has an access to edit the curriculum they made when needed. The atlas rubicon makes the mapping of curriculum like the class activities is written well.